Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 41762 by math khazana by abdo last updated on 12/Aug/18

let f(x) = ∫_0 ^1   ((ln(1+xt^2 ))/(1+t^2 )) dt  1) find a simple form of f(x)  2) calculate  ∫_0 ^1   ((ln(1+t^2 ))/(1+t^2 ))dt  3) calculate ∫_0 ^1   ((ln(1+2t^2 ))/(1+t^2 )) dt

letf(x)=01ln(1+xt2)1+t2dt1)findasimpleformoff(x)2)calculate01ln(1+t2)1+t2dt3)calculate01ln(1+2t2)1+t2dt

Commented by math khazana by abdo last updated on 13/Aug/18

we have f^′ (x)= ∫_0 ^1    (t^2 /((1+xt^2 )(1+t^2 )))dt  let decompose F(t) =(t^2 /((1+xt^2 )(1+t^2 )))  F(t)= ((at+b)/(t^2  +1)) +((ct +d)/(xt^2  +1))  F(−t)=F(t) ⇒((−at +b)/(t^2  +1)) +((−ct +d)/(xt^2  +1)) =F(t) ⇒  a=c=0⇒F(t)=(b/(t^2  +1)) +(d/(xt^2  +1))  lim_(t→+∞) t^2  F(t)=(1/x) =b  +(d/x) ⇒1=bx +d ⇒  d=1−bx ⇒F(t)=(b/(t^2  +1)) +((1−bx)/(xt^2  +1))  F(0) =0 =b +1−bx =(1−x)b +1 ⇒b=(1/(x−1))  d=1−(x/(x−1)) =((−1)/(x−1)) ⇒  F(t)=  (1/((x−1)(t^2  +1))) −(1/((x−1)(xt^2  +1))) ⇒  f^′ (x) =(1/(x−1)) ∫_0 ^1   (dt/(1+t^2 )) −(1/(x−1)) ∫_0 ^1    (dx/(1+xt^2 ))  =(π/(4(x−1))) −(1/(x−1)) ∫_0 ^1    (dt/(1+xt^2 ))  case1  x>0  changement t(√x)=u give  ∫_0 ^1     (dt/(1+xt^2 )) = ∫_0 ^(√x)     (1/(1+u^2 )) (du/(√x)) =(1/(√x)) arctan((√x))⇒  f^′ (x) =(π/(4(x−1))) −((arctan((√x)))/((x−1)(√x))) ⇒  f(x) =(π/4) ∫_0 ^x    (dt/(t−1))  − ∫_0 ^x     ((arctan((√t)))/((t−1)(√t))) +c  c=f(0)=0 ⇒f(x)=(π/4)ln∣x−1∣ −∫_0 ^x   ((arctan((√t)))/((t−1)(√t)))dt  but  ∫_0 ^x    ((arctan((√t)))/((t−1)(√t))) dt =_((√t)=u)   2∫_0 ^(√x)    ((arctan(u))/((u^2 −1)u)) udu  =2 ∫_0 ^(√x)    ((arctan(u))/(u^2 −1)) du ⇒  f(x)=(π/4)ln∣x−1∣ +2  ∫_0 ^(√x)     ((arctanu)/(1−u^2 )) du

wehavef(x)=01t2(1+xt2)(1+t2)dtletdecomposeF(t)=t2(1+xt2)(1+t2)F(t)=at+bt2+1+ct+dxt2+1F(t)=F(t)at+bt2+1+ct+dxt2+1=F(t)a=c=0F(t)=bt2+1+dxt2+1limt+t2F(t)=1x=b+dx1=bx+dd=1bxF(t)=bt2+1+1bxxt2+1F(0)=0=b+1bx=(1x)b+1b=1x1d=1xx1=1x1F(t)=1(x1)(t2+1)1(x1)(xt2+1)f(x)=1x101dt1+t21x101dx1+xt2=π4(x1)1x101dt1+xt2case1x>0changementtx=ugive01dt1+xt2=0x11+u2dux=1xarctan(x)f(x)=π4(x1)arctan(x)(x1)xf(x)=π40xdtt10xarctan(t)(t1)t+cc=f(0)=0f(x)=π4lnx10xarctan(t)(t1)tdtbut0xarctan(t)(t1)tdt=t=u20xarctan(u)(u21)uudu=20xarctan(u)u21duf(x)=π4lnx1+20xarctanu1u2du

Commented by math khazana by abdo last updated on 13/Aug/18

case 2  x<0  ∫_0 ^1     (dx/(1+xt^2 )) = ∫_0 ^1    (dt/(1−((√(−x))t)^2 ))  =_((√(−x))t =u)   ∫_0 ^(√(−x))     (1/(1−u^2 )) (du/(√(−x)))  =(1/(√(−x))) ∫_0 ^(√(−x))   (du/(1−u^2 )) = (1/(2(√(−x)))) ∫_0 ^(√(−x))   ((1/(1−u)) +(1/(1+u)))du  =(1/(2(√(−x))))[ln∣((1+u)/(1−u))∣]_0 ^(√(−x))  = (1/(2(√(−x))))ln∣((1+(√(−x)))/(1−(√(−x))))∣ ⇒  f^′ (x) = (π/(4(x−1))) −(1/(2(x−1)(√(−x))))ln∣((1+(√(−x)))/(1−(√(−x))))∣ ⇒  f(x)=(π/4)ln∣x−1∣ −∫  (1/(2(x−1)(√(−x))))ln∣((1+(√(−x)))/(1−(√(−x))))∣dx +c

case2x<001dx1+xt2=01dt1(xt)2=xt=u0x11u2dux=1x0xdu1u2=12x0x(11u+11+u)du=12x[ln1+u1u]0x=12xln1+x1xf(x)=π4(x1)12(x1)xln1+x1xf(x)=π4lnx112(x1)xln1+x1xdx+c

Commented by math khazana by abdo last updated on 13/Aug/18

2) let A = ∫_0 ^1   ((ln(1+t^2 ))/(1+t^2 ))dt    A=_(t=tanθ)    ∫_0 ^(π/4)    ((ln(1+tan^2 θ))/(1+tan^2 θ)) (1+tan^2 θ)dθ  = ∫_0 ^(π/4) ln((1/(cos^2 θ)))dθ =−2 ∫_0 ^(π/4) ln(cosθ)dθ    let H = ∫_0 ^(π/4) ln(cosθ)dθ  and K = ∫_0 ^(π/4) ln(sinθ)dθ  we have  H =_(θ=(π/2)−t)  −∫_(π/2) ^(π/4)   ln(sint)dt  = ∫_(π/4) ^(π/2)  ln(sint)dt = −∫_0 ^(π/4) ln(sint)dt +∫_0 ^(π/2) ln(sint)dt  =−K −(π/2)ln(2) ⇒ H +K =−(π/2)ln(2)   K−H = ∫_0 ^(π/4)  ln(sinθ)dθ −∫_0 ^(π/4) ln(cosθ)dθ  =∫_0 ^(π/4) ln(tanθ)dθ =_(tanθ =u)    ∫_0 ^1    ((ln(u))/(1+u^2 )) du  =∫_0 ^1 (Σ_(n=0) ^∞ (−1)^n u^(2n) )ln(u) du  =Σ_(n=0) ^∞   (−1)^n   ∫_0 ^1  u^(2n) ln(u)du  by parts  A_n = ∫_0 ^1 u^(2n) ln(u)du = [(1/(2n+1))u^(2n+1) ln(u)]_0 ^1   −∫_0 ^1    (1/((2n+1))) u^(2n) du =−(1/((2n+1)^2 )) ⇒  K−H = Σ_(n=0) ^∞    (((−1)^(n+1) )/((2n+1)^2 ))  = λ_0  ⇒  2K =−(π/2)ln(2) +λ_0  ⇒K =−(π/4)ln(2) +(λ_0 /2)  H =−(π/2)ln(2) −K =−(π/4)ln(2)−(λ_0 /2)

2)letA=01ln(1+t2)1+t2dtA=t=tanθ0π4ln(1+tan2θ)1+tan2θ(1+tan2θ)dθ=0π4ln(1cos2θ)dθ=20π4ln(cosθ)dθletH=0π4ln(cosθ)dθandK=0π4ln(sinθ)dθwehaveH=θ=π2tπ2π4ln(sint)dt=π4π2ln(sint)dt=0π4ln(sint)dt+0π2ln(sint)dt=Kπ2ln(2)H+K=π2ln(2)KH=0π4ln(sinθ)dθ0π4ln(cosθ)dθ=0π4ln(tanθ)dθ=tanθ=u01ln(u)1+u2du=01(n=0(1)nu2n)ln(u)du=n=0(1)n01u2nln(u)dubypartsAn=01u2nln(u)du=[12n+1u2n+1ln(u)]01011(2n+1)u2ndu=1(2n+1)2KH=n=0(1)n+1(2n+1)2=λ02K=π2ln(2)+λ0K=π4ln(2)+λ02H=π2ln(2)K=π4ln(2)λ02

Terms of Service

Privacy Policy

Contact: info@tinkutara.com